Method for obtaining thick brane models - Dutra, A. De Souza [UNESP]; De Brito, G. P. [UNESP]; Da Silva, J.M. Hoff [UNESP] (American Physical Society (APS), 2015)
In this work we present a new class of braneworld models, where the superpotential function may be decomposed in an specific form, which allows considerable simplifications in the field equations. We exemplify the method with two specific models that are extended versions of superpotentials already considered in the literature. As one can see in the examples, the braneworld scenarios obtained here present very interesting features, such as a split-brane mechanism and an asymmetric warp factor shape, which is essential for addressing the hierarchy problem in the context of thick-brane scenarios.